0195 Social Determinants of Sleep: Inside Relationships with Significant Others. (27th May 2020) - Mousavi, Z; Tran, M; Kuhlman, K R
Abstract: Introduction: Social relationships impact health through different mechanisms. Sleep problems are prevalent among adults in the USA, negatively impacting all-cause mortality, and increasing the risk for chronic diseases such as depression, cardiovascular disease, and cancer. This study aimed to assess whether the quality of an individual's relationship with their significant other including support and strain, subjective relationship quality, joint decision making, marital risk, and conflict are associated with clinical, subjective, and objective measures of sleep. Methods: Participants were selected from the Midlife in the United States (MIDUS) study if they had complete data on subjective sleep quality from the MIDUS II biomarker project and shared a bed with their partner ( n =751, 49.5% female, M age =53.4, SD age =11.2, range= 34–83). Subjective sleep quality was measured using the PSQI. A subset of these participants ( n =246, 50.8% female) also completed 7-days of daily diary and actigraphy. Results: Sleep disturbances were pervasive; 44.1% ( n =331) of participants reported clinically meaningful sleep disturbances (PSQI>=5). Among the smaller sample of participants with 7-day sleep data, sleep disturbances were even more prevalent (60.9%). There were significant bivariate associations between higher support and lower strain with better subjectively and objectively sleep outcomes. Better subjective relationship quality was also associated with better subjectively measured sleep outcomes. Higher marital risk and more disagreement with partner were associated with poorer sleep. When accounting for all marital relationship factors, participants with higher support and lower strain given to partner had a better long-term sleep quality, b = 1.93, SE = .54, p <.001. Relationship quality was also associated with better daily sleep quality and daily reports of feeling rested, b = -.12, SE = .05, p =.023, and b = .11, SE = .048, p =.023, respectively. These relationships remained significant after accounting for age, current employment status, recent major health events, average daily caffeine, alcohol, exercise, and napping. Conclusion: These findings support the importance of considering social determinants of sleep, suggesting that relationships with significant others may impact health through sleep quality. This highlights the importance of sleep as a transdiagnostic physiological mechanism that could be enhanced through improvements to relationships with significant others. Support: N/A